2018
DOI: 10.1002/anie.201804885
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Translational Backbone Engineering through Selenomethionine‐Mediated Incorporation of Freidinger Lactams

Abstract: Amino-γ-lactam (Agl) bridged dipeptides, commonly known as Freidinger lactams, have been shown to constrain peptide backbone topology and stabilize type II' β-turns. The utility of these links as peptide constraints has inspired new approaches to their incorporation into complex peptides and peptoids, all of which require harsh reaction conditions or protecting groups that limit their use on unprotected peptides and proteins. Herein, we employ a mild and selective alkylation of selenomethionine in acidic aqueo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Many of the inherent limitations of DNA as the encoding element of DEL can be overcome through immobilization, and an approach termed reversible adsorption to solid support (RASS) has been developed to facilitate the covalent manipulation of macromolecules such as proteins and DNA in organic solvents . Non‐DNA encoding strategies, namely peptide nucleic acids (PNAs) can also be employed to overcome the inherent limitations of DNA as a encoding tag .…”
Section: Figurementioning
confidence: 99%
“…Many of the inherent limitations of DNA as the encoding element of DEL can be overcome through immobilization, and an approach termed reversible adsorption to solid support (RASS) has been developed to facilitate the covalent manipulation of macromolecules such as proteins and DNA in organic solvents . Non‐DNA encoding strategies, namely peptide nucleic acids (PNAs) can also be employed to overcome the inherent limitations of DNA as a encoding tag .…”
Section: Figurementioning
confidence: 99%
“…Many of the inherent limitations of DNA as the encoding element of DEL can be overcome through immobilization, and an approach termed reversible adsorption to solid support (RASS) has been developed to facilitate the covalent manipulation of macromolecules such as proteins and DNA in organic solvents . Non‐DNA encoding strategies, namely peptide nucleic acids (PNAs) can also be employed to overcome the inherent limitations of DNA as a encoding tag .…”
Section: Figurementioning
confidence: 99%
“…[19][20][21][71][72][73][74][75] This approach has also been applied to biomacromolecules to perform challenging synthetic modifications in an approach described as reversible adsorption to solid support (RASS). [76,77] As RASS based reactions mostly mimic typical organic conditions utilizing dry solvents and high concentrations of reagents, the Dawson and Baran groups envisioned the adaption of this technology to DEL to enable previously sluggish chemical reactivities. [78] They demonstrated that immobilizing DNA onto an inert, non-swelling, polystyrene-based quaternary ammonium support facilitates the rapid development of useful transformations including C (sp 2 )-C(sp 3 ) decarboxylative cross-couplings, the first DNAcompatible electrochemical reactions, and improved reductive amination conditions.…”
Section: Emerging Techniquesmentioning
confidence: 99%